Teaching Area and Volume to Students With Mild Intellectual Disability. (August 2015) - Hord, Casey; Xin, Yan Ping
In the current educational climate, teachers are required to find methods to give all students, including students with mild intellectual disability, access to the general education curriculum. The purpose of this study was to investigate the combined effects of the concrete−semiconcrete−abstract instructional sequence and model-based problem solving to teach area and volume to sixth-grade students with mild intellectual disability. The researchers in this study utilized a multiple probe design, a variation of the multiple baseline design, to establish the functional relationship between the intervention and students' performance on area and volume problems. The participants solved a high percentage of the sixth-grade-level problems addressed on the criterion tests, but success with more complex problems will be necessary for proficiency at grade level with the Common Core Standards for Mathematics.